ANALISIS RESEPSI MASYARAKAT BULUKUMBA TERHADAP BERITA PILKADA DI HARIAN RADAR SELATAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The dissemination of information in the South Radar Daily which focuses on the 2020 Bulukumba Pilkada news forms the mindset of the people and influences public opinion, therefore the researcher considers the reception of the Pilkada news to be investigated from the perspective of the Bulukumba people's interpretation so that it attracts researchers to raise it with the aim of this research. The purpose of this study was to find out the interpretation and decoding of several people who became informants so that they could get a reception from the people of Bulukumba on the news of the Pilkada in the South Radar Daily. This researcher uses a qualitative descriptive type of research by approaching the science of communication and collecting data from observations, interviews, and documentation. This study uses Stuart Hall's reception theory which is divided into three categories of interpretation, namely dominant hegemony, negotiation, and opposition. There were five informants in this study, namely the Bulukumba people who were then drawn from each profession such as the South Radar Daily Leader, Panwaslu, TPS Committee, Non-Governmental Organizations, and Community Leaders. The results of the research found by the researchers during their research in the field showed that some of the Bulukumba people who were informants had various receptions from the news of the Pilkada in the South Radar Daily according to the experience and knowledge of each resource person. of the five informants who have been interviewed, three sources namely Sunarti Sain, S.E, Al Ihwal, S.Pd, and A. Trisnawati are in the position of Dominant Hegemony or the position of receiving. One informant, namely Syahrul, is in a negotiating position, meaning that he is still comparing the content of the news presented by the South Radar Daily with other media and another informant, Kamaruddin, is in an opposition position, which is refusing to report the election in the South Radar Daily. dominantly made the South Radar Daily print media as the main reference for selecting the candidates for the Regent and Deputy Regent of Bulukumba in 2020. The implication of this research is that the South Radar Daily is expected to remain independent in presenting reliable actual news, especially on the Pilkada news so that the truth can be accounted for and the Bulukumba community is expected to be able to respond to the news that is published wisely so that it can have a good impact on its readers.